The effects of a small scale intervention to develop self-regulation in kindergarten children. Issue 3 (17th February 2020) - Shiu, Shiou-Ping; Wang, Sze-Han; Chen, Yu-Jun
ABSTRACT: This study used a quasi-experimental design to test if a small scale intervention improved self-regulation with 94 kindergarten children in Taiwan. The purpose of this study was to draw on the theory of Vygotsky and examine activities that could fit into the class schedule without substantially changing the basic curriculum and would require minimal training for implementation. The results showed there was a significant difference in self-regulation gains between the treatment and control groups in the overall sample. It suggests that a small-scale intervention with external mediators (microphone, play plan and clean-up song) and pattern movement game (circle games) is sufficient for improving self-regulation. Moreover, the qualitative data showed that the mediators such as writing a play plan and clean-up songs created opportunities for children to engage in self-directing activities and increasing autonomy.